Gold nanoparticle assisted synthesis of MoS2 monolayers by chemical vapor deposition. Issue 16 (23rd July 2021) - Seravalli, L.; Bosi, M.; Fiorenza, P.; Panasci, S. E.; Orsi, D.; Rotunno, E.; Cristofolini, L.; Rossi, F.; Giannazzo, F.; Fabbri, F.
Abstract : We present a complete study of the CVD synthesis of monolayer MoS2 assisted by gold nanoparticles, resulting in (i) improved lateral growth, (ii) quenched exciton PL emission, and (iii) a positive threshold voltage in back-gated FETs. Abstract : The use of metal nanoparticles is an established paradigm for the synthesis of semiconducting one-dimensional nanostructures. In this work we study their effect on the synthesis of two-dimensional semiconducting materials, by using gold nanoparticles for chemical vapor deposition growth of two-dimensional molybdenum disulfide (MoS2 ). In comparison with the standard method, the employment of gold nanoparticles allows us to obtain large monolayer MoS2 flakes, up to 20 μm in lateral size, even if they are affected by the localized overgrowth of MoS2 bilayer and trilayer islands. Important modifications of the optical and electronic properties of MoS2 triangular domains are reported, where the photoluminescence intensity of the A exciton is strongly quenched and a shift to a positive threshold voltage in back-gated field effect transistors is observed. These results indicate that the use of gold nanoparticles influences the flake growth and properties, indicating a method for possible localized synthesis of two-dimensional materials, improving the lateral size of monolayers and modifying their properties.